2007
DOI: 10.1088/0022-3727/40/16/023
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, optical and structural properties of CuCrO2films prepared by pulsed laser deposition

Abstract: Transparent conducting CuCrO2 thin films were prepared by pulsed laser deposition (PLD) from a nanocrystalline CuCrO2 target. The derived CuCrO2 films were highly c-axis oriented deposited at 800 K. The microstructural, electrical as well as optical properties were studied. It was found that the films were relatively smooth and behaved as semiconductors. The energy band of the CuCrO2 films is constructed based on the Mott–Davis model in order to investigate the conduction mechanism. The transmittances of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 14 publications
7
49
1
1
Order By: Relevance
“…For all three methods, the VBM is located on the K to G line, near K, with the CBM found on the M-G line, indicating that CuCrO 2 is an indirect band gap material, and not a direct band gap materials as had been suggested previously. 43 The calculated indirect band gaps are 1.06 eV, 2.06 eV and 3.09 eV using PBE, PBE + U and HSE06 respectively. The PBE calculated band structure features are visibly different to those of the PBE + U and HSE06 band structure, possessing a much less dispersive valence band.…”
Section: B Electronic Structurementioning
confidence: 96%
See 1 more Smart Citation
“…For all three methods, the VBM is located on the K to G line, near K, with the CBM found on the M-G line, indicating that CuCrO 2 is an indirect band gap material, and not a direct band gap materials as had been suggested previously. 43 The calculated indirect band gaps are 1.06 eV, 2.06 eV and 3.09 eV using PBE, PBE + U and HSE06 respectively. The PBE calculated band structure features are visibly different to those of the PBE + U and HSE06 band structure, possessing a much less dispersive valence band.…”
Section: B Electronic Structurementioning
confidence: 96%
“…43 The earliest recorded measurement of the band gap of CuCrO 2 was carried out by Benko and Koffyberg, 40 who found that it possessed an indirect band gap of 1.28 eV, with an indirect allowed transition at 3.08 eV and a direct allowed transition at 3.35 eV. A further interband transition at $2.20 eV was noted, although the authors were not able to determine the transition type.…”
mentioning
confidence: 99%
“…The extracted direct band gap E g is found to be between 3.1 and 3.3 eV, which is in very good agreement with previous experimental and theoretical studies. 16,32,33,36,38,40,43,46,47 The figure of merit (FOM) for a ratio of w = 0.5 is calculated. FOM is defined as:…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Copper chromium oxides contrast with other delafossites, in terms of: (i) high density of state of 3d M cations (Cr 3+ ) near the valence band maximum, (ii) covalent mixing between chromium and oxygen ions and (iii) good dopability, [17][18][19][20][21][22] making CuCrO 2 a good p-type candidate for transparent electronic devices. Several methods were reported in the literature for the synthesis of CuCrO 2 : solid-state reaction (SS), 17,[20][21][22][23][24][25][26][27][28][29][30] sol-gel (SG), [31][32][33][34][35][36][37] pulsed laser deposition (PLD), [38][39][40][41][42] magnetron sputtering (MS) 16,[43][44][45][46] and chemical vapor deposition (CVD) including spray pyrolysis. [47][48][49][50] A summary of the electrical and optical properties versus the synthesis methods and the process temperature is given in are obtained with the films deposited by sol-gel, due to the low carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Above 220 K the small polaron hopping (SPH) model is used to fit the data and a hopping activation energy W of 65 meV is calculated, which is comparable to Boltzmann activation energies previously obtained. 30 At approximately 220 K there is a discernible change in the slope of the line which indicates a crossover in the conduction mechanism. The inset of Fig.…”
mentioning
confidence: 96%